ANALYSIS OF FIGURATIVE LANGUAGE IN WESTLIFE SONGS - Mukhlasul Fasikh; Jire Jordan Siahaan; Chandra Ivan (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
The purpose of this research is to analyze the Figurative Language as well as the meanings from Westlife songs. In this research, the researchers used qualitative data collection methods and data analysis from different sources as the main of this research method. The data is divided into 2 things such as primary data and secondary data. The technique of collecting data that the researchers used is from journal, article, e-book, credible website. The techniques of analyzing data that the researchers used are reading the song lyrics, identifying the figurative languages, classifying the data coding, interpreting, drawing the conclusion, and writing the report. Based on the result finding, the most figurative language in those two languages are Metaphor and Hyperbole. People are expected to maintain their relationship with one another. The lyrics in these songs are very encouraging to people who are in the relationship. It is expected to maintain people’s relationship well. Through this research, people can be helped to understand figurative languages in the songs with the right meaning as well as to encourage learning English.